STAT3 gain-of-function syndrome - Vogel, Tiphanie P.; Leiding, Jennifer W.; Cooper, Megan A.; Forbes Satter, Lisa R. (Frontiers in Pediatrics, 2023)
STAT3 gain-of-function (GOF) syndrome is a multi-organ primary immune regulatory disorder characterized by early onset autoimmunity. Patients present early in life, most commonly with lymphoproliferation, autoimmune cytopenias, and growth delay. However, disease is often progressive and can encompass a wide range of clinical manifestations such as: enteropathy, skin disease, pulmonary disease, endocrinopathy, arthritis, autoimmune hepatitis, and rarely neurologic disease, vasculopathy, and malignancy. Treatment of the autoimmune and immune dysregulatory features of STAT3-GOF patients relies heavily on immunosuppression and is often challenging and fraught with complications including severe infections. Defects in the T cell compartment leading to effector T cell accumulation and decreased T regulatory cells may contribute to autoimmunity. While T cell exhaustion and apoptosis defects likely contribute to the lymphoproliferative phenotype, no conclusive correlations are yet established. Here we review the known mechanistic and clinical characteristics of this heterogenous PIRD.